The durability of vaccine-induced protection: an overview - Vipin M. Vashishtha; Puneet Kumar (Taylor & Francis Group, 2024)
ABSTRACTIntroduction Current vaccines vary widely in both their efficacy against infection and disease, and the durability of the efficacy. Some vaccines provide practically lifelong protection with a single dose, while others provide only limited protection following annual boosters. What variables make vaccine-induced immune responses last? Can breakthroughs in these factors and technologies help us produce vaccines with better protection and fewer doses? The durability of vaccine-induced protection is now a hot area in vaccinology research, especially after COVID-19 vaccines lost their luster. It has fueled discussion on the eventual utility of existing vaccines to society and bolstered the anti-vaxxer camp. To sustain public trust in vaccines, lasting vaccines must be developed.Areas covered This review summarizes licensed vaccines' protection. It analyses immunological principles and vaccine and vaccinee parameters that determine longevity of antibodies. The review concludes with challenges and the way forward to improve vaccine durability.Expert opinion Despite enormous advances, we still lack essential markers and reliable correlates of lasting protection. Most research has focused on humoral immune responses, but we must also focus on innate, mucosal, and cellular responses - their assessment, correlates, determinants, and novel adjuvants. Suitable vaccine designs and platforms for durable immunity must be found.